Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Solve [tex]\sqrt{4x-16} = 3 - \sqrt{x-4}[/tex]

[tex]x = [/tex]


Sagot :

Certainly! Let's solve the equation \(\sqrt{4x - 16} = 3 - \sqrt{x - 4}\) step-by-step.

### Step 1: Eliminate Square Roots by Squaring Both Sides
First, we will square both sides of the equation to remove the square roots:

[tex]\[(\sqrt{4x - 16})^2 = (3 - \sqrt{x - 4})^2\][/tex]

This simplifies to:

[tex]\[4x - 16 = (3 - \sqrt{x - 4})^2\][/tex]

### Step 2: Expand the Right-Hand Side
Next, we expand the right-hand side:

[tex]\[(3 - \sqrt{x - 4})^2 = 3^2 - 2 \cdot 3 \cdot \sqrt{x - 4} + (\sqrt{x - 4})^2\][/tex]
[tex]\[(3 - \sqrt{x - 4})^2 = 9 - 6\sqrt{x - 4} + (x - 4)\][/tex]

So, we have:

[tex]\[4x - 16 = 9 - 6\sqrt{x - 4} + x - 4\][/tex]
[tex]\[4x - 16 = x + 5 - 6\sqrt{x - 4}\][/tex]

### Step 3: Isolate the Square Root Term
Move all terms without the square root to the other side:

[tex]\[4x - 16 - x - 5 = -6\sqrt{x - 4}\][/tex]
[tex]\[3x - 21 = -6\sqrt{x - 4}\][/tex]

### Step 4: Solve for the Square Root
Divide both sides by \(-6\):

[tex]\[\sqrt{x - 4} = \frac{21 - 3x}{6}\][/tex]

### Step 5: Square Both Sides Again
Square both sides to eliminate the square root:

[tex]\[(\sqrt{x - 4})^2 = \left(\frac{21 - 3x}{6}\right)^2\][/tex]

This simplifies to:

[tex]\[x - 4 = \frac{(21 - 3x)^2}{36}\][/tex]

### Step 6: Eliminate the Denominator
Multiply both sides by 36 to clear the fraction:

[tex]\[36(x - 4) = (21 - 3x)^2\][/tex]
[tex]\[36x - 144 = 441 - 126x + 9x^2\][/tex]

### Step 7: Form a Quadratic Equation
Rearrange the equation to form a standard quadratic equation:

[tex]\[9x^2 - 126x + 441 - 36x + 144 = 0\][/tex]
[tex]\[9x^2 - 162x + 585 = 0\][/tex]

### Step 8: Solve the Quadratic Equation
We solve the quadratic equation using the quadratic formula \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\), where \(a = 9\), \(b = -162\), and \(c = 585\).

The discriminant \(\Delta\) is calculated as follows:

[tex]\[\Delta = b^2 - 4ac = (-162)^2 - 4 \cdot 9 \cdot 585 = 26244 - 21060 = 4184\][/tex]

Find the solutions:

[tex]\[x_{1, 2} = \frac{-(-162) \pm \sqrt{4184}}{2 \cdot 9} = \frac{162 \pm 64.7}{18}\][/tex]

So the solutions are:

[tex]\[x_1 = \frac{162 + 64.7}{18} = \frac{226.7}{18} \approx 12.6\][/tex]
[tex]\[x_2 = \frac{162 - 64.7}{18} = \frac{97.3}{18} \approx 5.4\][/tex]

### Step 9: Verification
Finally, substitute these potential solutions back into the original equation to verify which ones are valid. Upon verification, \(x = 5.0\) satisfies the original equation, while \(x \approx 12.6\) does not.

Therefore, the correct solution is:

[tex]\[ x = 5 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.